Symptomatic menopausal transition and risk of subsequent stroke - Yu,Chao-Hung; Kor,Chew-Teng; Weng,Shuo-Chun; Chang,Chia-Chu; Chen,Ching-Pei; Wu,Chia-Lin (PeerJ, 2019)
Objective To examine the long-term risk of stroke in women who have experienced symptomatic menopausal transition. Methods In this nationwide, population-based cohort study conducted from January 1, 2000 to December 31, 2013, we identified 22,058 women with no prior history of stroke, who experienced symptomatic menopausal transition at ≥45 years of age. Moreover, 22,058 women without symptomatic menopause were matched by propensity scores and enrolled as a comparison group. The propensity score was calculated by using all characteristic variables of each subject, including demographics (age and monthly income), comorbidities (hypertension, hyperlipidemia, diabetes mellitus, obesity, chronic kidney disease, coronary artery disease, congestive heart failure, chronic obstructive pulmonary disease, dysrhythmia, peripheral artery occlusive disease), Charlson’s comorbidity index score, clinic visit frequency, and long-term medications (antihypertensives, antidiabetic agents, statins, antiplatelets, aspirin, warfarin, and hormone replacement therapy). The primary endpoint was the development of stroke after the onset of symptomatic menopausal transition. The Fine and Gray’s proportional subhazards model was performed to assess the association between symptomatic menopausal transition and subsequent stroke. All subjects were followed up until December 31, 2013. Results During a mean follow-up of 8.5 years (standard deviation 4.7 years, maximum 14 years), 2,274 (10.31%) women with symptomatic menopausal transition, and 1,184 (5.37%) matched comparison participants developed stroke. The incidence rates were 11.17 per 1,000 person-years in the symptomatic menopausal transition group compared with 8.57 per 1,000 person-years in the comparison group. The risk of developing stroke was significantly higher in women with symptomatic menopausal transition (crude subhazard ratio, 1.31; 95% confidence interval (CI) [1.22–1.41]; P < 0.001). After adjusting for demographics, comorbidities, clinic visit frequency, and long-term medications, the risk of stroke remained statistically significant (adjusted subhazard ratio, 1.30; 95% CI [1.21–1.40]; P < 0.001). Moreover, subgroup analyses revealed no evidence for inconsistent effects for symptomatic menopausal transition on subsequent risk of stroke across all subgroups except age, comorbidities, hypertension, and use of antihypertensives. Women with early menopausal transition (before age 50), without comorbid condition, without hypertension, or without use of antihypertensives are at a higher risk of stroke. The longer duration of symptomatic menopausal transition was associated with higher risk of stroke (P for trend < 0.001). Conclusion In this large-scale retrospective cohort study, symptomatic menopausal transition was statistically significantly associated with a 30% increased risk of stroke. Further prospective studies are required to confirm our findings.
Keywords: Menopause; Stroke; Transition; Women